Diseño de un sistema de enfriamiento para el fluido de perforación de los equipos de perforación profunda del Instituto Costarricense de Electricidad - Rojas-Acosta, Osvaldo (Instituto Tecnológico de Costa Rica, 2014)
This project was developed at the Center for Geothermal Resources Services of the Costa Rican Electricity Institute, located in the foothills of the Rincon de La Vieja. It was to develop a proposed design of a cooling system for fluids deep drilling, with the aim of developing a smaller one which allows the reduction of the initial temperature of the slurry from 85 ° C to an acceptable range of 55 to 58 ° C. In the first instance a diagnosis of the current situation was developed and it was determined that the current requirements for temperature, cooling tower not doing its job; but with modifications can increase the mud inlet temperature to the cooling tower in 4 ° C. The proposed solution is a thermal and hydraulic design of heat exchangers, shell and tube that would meet the requirements of temperature decrease, ie twice improve the functioning of existing cooling equipment. It also eradicates other shortcomings of the current system and that reflect potential savings in additives for the preparation of drilling fluids. Because the requirement for cooling the drilling fluid is very high and the dimensions for your new computer are very low, two heat exchangers in series were designed to meet that need with a cost of materials for economic development within the field of deep drilling.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2014.
Keywords: Potencial eléctrico; Diseño y construcción; Tratamiento térmico; Sistemas de enfriamiento; Hidráulica subterránea